Edukasi Terhadap Pencegahan Narkoba, Dampak Penggunaan Tato dan Kasus Bullying di SMP Negeri 1 Simpang Rimba - Miftakhi, Diah Rina; Wardani, Erika Fitri; Medyharto (Jurnal Pengabdian Tri Bhakti, 2025)
This Community Service (PKM) activity integrated with the Real Work Lecture (KKN) aims to increase the knowledge, awareness, and attitudes of adolescents towards three crucial issues among students: drug abuse, the impact of tattoo use, and the prevention of bullying behavior. This program was implemented at Simpang Rimba 1 State Junior High School by lecturers from the Muhammadiyah University of Bangka Belitung, namely Diah Rina Miftakhi and Erika Fitri Wardani, in collaboration with the Social Service of the Bangka Belitung Islands Province represented by Mr. Medyharto. The methods used included interactive lectures, presentations of materials, discussions, and questions and answers with all participants. The results of the activity showed an increase in the level of understanding and awareness of students regarding the dangers of drugs, the health risks of tattoo use, and the importance of building a bullying-free school environment. This program strengthens the synergy between universities, local governments, and educational institutions in building the character of a young generation that is intelligent, healthy, resilient, and has good morals.